Effectiveness of Bortezomib in Cardiac AL Amyloidosis: A Report of Two Cases. (10th March 2014) - Nigrelli, Santi; Curciarello, Giuseppe; Ballo, Piercarlo; Michelassi, Stefano; Pizzarelli, Francesco
Abstract : Cardiac involvement is a major prognostic determinant in patients with primary AL amyloidosis. The clinical results of standard therapeutic approaches are suboptimal. It has been recently shown that bortezomib, an inhibitor of the proteasome, can induce rapid favourable responses in AL amyloidosis improving cardiac function and survival. Herein we report on two patients with cardiac amyloidosis treated by bortezomib who experienced partial or total remission of hematologic disease and of cardiac involvement. However, death of one patient, suffering from chronic kidney disease stage 5, due to fulminant respiratory syndrome suggests the need for caution in bortezomib use if patients have this comorbid condition.